2019
DOI: 10.1002/slct.201804003
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Copper Nanoparticles Supported on Zeolite Y and its Application in Catalytic C‐N Cross Coupling Reactions between Amines and Aryl halides

Abstract: A biosynthesis of Copper Nanoparticles supported on Zeolite Y and its application as efficient, reusable, heterogeneous catalyst in C−N cross coupling reactions between amines and aryl halides are reported. The biosynthesis of CuNPs/Zeolite Y was achieved by the reduction of CuSO4.5H2O with the lemon juice (without peal) and encapsulated into the Zeolite Y in a single step. In this biosynthetic method, the ascorbic acid present in the lemon juice acted as a reducing agent for CuSO4.5H2O. The CuNPs/Zeolite Y wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…The supporting information contains the detailed process for the synthetic methodology of 1-MeIm IL@ZY-Fe 3 O 4 , characterization techniques, spectroscopic data of all synthesized compounds and 1 H NMR, 13 C NMR and Mass analysis.…”
Section: Supporting Information Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…The supporting information contains the detailed process for the synthetic methodology of 1-MeIm IL@ZY-Fe 3 O 4 , characterization techniques, spectroscopic data of all synthesized compounds and 1 H NMR, 13 C NMR and Mass analysis.…”
Section: Supporting Information Summarymentioning
confidence: 99%
“…[3][4][5] In addition, zeolite-Y or its loaded with transition metals is increasingly an ideal support for homogeneous catalysts such as acidic liquid groups, ionic liquids, [6][7][8][9] bi-functional magnetic nanocatalysts, [10] bi-functional core-shell molecular sieves [11] and efficient catalysts have been used in the fabrication of organic and heterocyclic compounds. [12][13][14] To the best of our knowledge, the use of imidazolium chloride ionic liquid on the surface of magnetic zeolite-Y as an efficient multifunctional nanocatalyst in the synthesis of N-benzimidazole or benothiazole thiazolidines has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Pandian et al [ 208 ] reported the green synthesis of Cu NPs through the reduction of CuSO 4 .5H 2 O with the lemon juice (without peal) and their immobilization on Zeolite Y as a support (and their encapsulation into the Zeolite Y) in a single step. In this biosynthetic approach, the ascorbic acid present in the lemon juice was used as a reductant for CuSO 4 .5H 2 O.…”
Section: Copper Nanocatalystsmentioning
confidence: 99%
“…Zeolites are crucial solid catalysts that have been utilized in several types of reactions such as cracking, 5,12–18 isomerization, 19–21 alkylation, 22 combustion, cross-coupling, 23 oligomerization, 24 and more. 25–31 Numerous zeolitic materials have been proven to have superior activity in the cracking reaction.…”
Section: Introductionmentioning
confidence: 99%